2020
DOI: 10.3390/molecules25030501
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Activity of Oxypeucedanin via Induction of G2/M Phase Cell Cycle Arrest and p53-Dependent MDM2/p21 Expression in Human Hepatoma Cells

Abstract: Oxypeucedanin (OPD), a furocoumarin compound from Angelica dahurica (Umbelliferae), exhibits potential antiproliferative activities in human cancer cells. However, the underlying molecular mechanisms of OPD as an anticancer agent in human hepatocellular cancer cells have not been fully elucidated. Therefore, the present study investigated the antiproliferative effect of OPD in SK-Hep-1 human hepatoma cells. OPD effectively inhibited the growth of SK-Hep-1 cells. Flow cytometric analysis revealed that OPD was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Given that the cell cycle plays a vital role in cell proliferation, 38 flow cytometric analysis was performed to measure the cell cycle distribution. Downregulation of Bcl2l2‐Pabpn1 arrested the cell cycle at the G2‐M phase in glioblastoma cells (Figure 4F,G), indicating that reduced proliferation activity induced by Bcl2l2‐Pabpn1 deficiency might be related to G2‐M phase cell cycle arrest 39 . Additionally, cell apoptosis was significantly promoted by Bcl2l2‐Pabpn1 knockdown using flow cytometry (Figure 4H,I).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that the cell cycle plays a vital role in cell proliferation, 38 flow cytometric analysis was performed to measure the cell cycle distribution. Downregulation of Bcl2l2‐Pabpn1 arrested the cell cycle at the G2‐M phase in glioblastoma cells (Figure 4F,G), indicating that reduced proliferation activity induced by Bcl2l2‐Pabpn1 deficiency might be related to G2‐M phase cell cycle arrest 39 . Additionally, cell apoptosis was significantly promoted by Bcl2l2‐Pabpn1 knockdown using flow cytometry (Figure 4H,I).…”
Section: Resultsmentioning
confidence: 91%
“…Downregulation of Bcl2l2-Pabpn1 arrested the cell cycle at the G2-M phase in glioblastoma cells (Figure 4F,G), indicating that reduced proliferation activity induced by Bcl2l2-Pabpn1 deficiency might be related to G2-M phase cell cycle arrest. 39 Additionally, cell apoptosis was significantly promoted by Bcl2l2-Pabpn1 knockdown using flow cytometry (Figure 4H,I). We further explored whether Bcl2l2-Pabpn1 participates in the motility of glioblastoma cells.…”
Section: Promotion Of Glioblastoma Progression By Bcl2l2-pabpn1 Fusio...mentioning
confidence: 94%
“…Column chromatography on silica gel (CC) has been used for the isolation of OP from the root methanolic fraction of A. dahurica [ 16 , 17 , 18 ]. This compound has been isolated from ethanolic and n -butanol (BuOH)-soluble partitions of this species by exploiting CC [ 19 ] and recrystallization [ 20 ], respectively; as well as from the CHCl 3 and CH 2 Cl 2 soluble fractions using CC [ 21 ] and recrystallization methods [ 22 ], and CC on silica gel [ 23 , 24 ], respectively.…”
Section: Phytochemical Studies Of Oxypeucedaninmentioning
confidence: 99%
“…Notably, the root part of ADR has been characterized as the richest natural source of oxypeucedanin [ 6 ]. Previous studies have indicated that oxypeucedanin have various biological activities including antiarrhythmic activity, anti-oxidant, anti-inflammatory, analgesic, anti-cancer, and antibacterial effects [ 6 , 7 , 8 , 9 ]. Furthermore, oxypeucedanin was reported to be a potentially effective intervention for nephrotoxicity induced by sunitinib [ 10 ].…”
Section: Introductionmentioning
confidence: 99%